2010
DOI: 10.1007/s00253-010-2756-3
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective hydroxylation of norisoprenoids by CYP109D1 from Sorangium cellulosum So ce56

Abstract: Sesquiterpenes are particularly interesting as flavorings and fragrances or as pharmaceuticals. Regio- or stereoselective functionalizations of terpenes are one of the main goals of synthetic organic chemistry, which are possible through radical reactions but are not selective enough to introduce the desired chiral alcohol function into those compounds. Cytochrome P450 monooxygenases are versatile biocatalysts and are capable of performing selective oxidations of organic molecules. We were able to demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 53 publications
6
49
0
Order By: Relevance
“…Therefore, we investigated 10 P450s from S. cellulosum-a bacterium typically found in soil (Shimkets et al, 2006), where it is exposed to a variety of xenobiotics-for their ability to convert tricyclic drugs. Terpenes and terpenoids as well as fatty acids have already been identified as substrates for these wild-type P450s in previous studies (Khatri et al, 2010a(Khatri et al, ,b, 2014Ly et al, 2012;Schifrin et al, 2014). Moreover, 4-methyl-3-phenyl-coumarin, a tricyclic molecule, was identified as a substrate for CYP264A1 .…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Therefore, we investigated 10 P450s from S. cellulosum-a bacterium typically found in soil (Shimkets et al, 2006), where it is exposed to a variety of xenobiotics-for their ability to convert tricyclic drugs. Terpenes and terpenoids as well as fatty acids have already been identified as substrates for these wild-type P450s in previous studies (Khatri et al, 2010a(Khatri et al, ,b, 2014Ly et al, 2012;Schifrin et al, 2014). Moreover, 4-methyl-3-phenyl-coumarin, a tricyclic molecule, was identified as a substrate for CYP264A1 .…”
Section: Discussionmentioning
confidence: 78%
“…For the past few years, we have been engaged in the study of novel P450s from myxobacteria, and some P450s from S. cellulosum So ce56 have shown a potential for industrial and biotechnological applications (Khatri et al, 2010a(Khatri et al, ,b, 2013(Khatri et al, , 2014Ly et al, 2012;Ringle et al, 2013). We were also able to develop an efficient E. coli-based whole-cell bioconversion system for some myxobacterial P450s .…”
Section: Discussionmentioning
confidence: 99%
“…Spectral dissociation constants were determined as described previously Khatri et al, 2010). A double beam UV/VIS spectrometer (Lambda 35, PerkinElmer, Germany) was equipped with two tandem quartz cuvettes (Hellma, Germany).…”
Section: Determination Of Spectral Dissociation Constantsmentioning
confidence: 99%
“…As a result, it was confirmed that the active forms of VD 3 were produced when the R. erythropolis cell was used. It has been reported that the redox partner that is capable of most efficiently supplying the electrons to P450 is not necessarily the protein with which P450 couples in the cell of the original organism [7] . This is thought to be because the electron transfer efficiency is affected drastically by the slight difference in the intracellular environment or the intracellular expression level of the gene.…”
Section: Intracellular Conversion Using the Recombinant Expressionmentioning
confidence: 99%